Understandability of the software engineering method as an important factor for selecting a CASE tool - Rozman, Ivan (Informatica (Ljubljana), 1992)
The paper highlights the understandability of a software engineering methodology as an important criterion for selecting a CASE tool. This aspect is treated through the comparison of learning properties of two very well known methodologies on which CASE tools are usually based. The first one is SASD and the second one JSD. A group of engineers was tested with the purpose to compare the two methodologies. Each engineer had to write a seminar, fill in our questionnaire and explain his observations. At the end of the paper a general conclusion is given.
Keywords: computer science; računalništvo; programska oprema; razvoj; programsko inženirstvo; CASE orodja